Power quality improvement using series APF based on multi-level (NPC) inverter topologies with intelligent control approaches - Chennai Salim (University of Eloued جامعة الوادي, 2023)
This paper presents the performance of novel configuration of series active power filter (Series APF) based on five-level neutral point clamped (NPC) using modified instantaneous reactive power theory control strategy with fuzzy control scheme. The series filter is adopted to decrease voltage harmonics, compensate all voltage disturbances and regulate the terminal voltage of the load. The series APF injects a voltage component in series with supply voltage which is added or subtracted from the source voltage thus maintaining the load side waveforms as pure sinusoidal. Multi-level inverters are currently being investigated and used in various industrial applications. Five-level (NPC) inverter topology is one of the most converters employed in medium and high power applications, their advantages include the capability to reduce the harmonic content and decrease the voltage or current ratings of the semiconductors. On the other hand intelligent techniques know today a great use, due to the advantages that offers compared to conventional techniques. To benefit of these advantages efficient control scheme for series APF using this techniques is proposed in this work. The fuzzy voltage controller is designed to improve compensation capability of series active power filter by adjusting the voltage error using a fuzzy rule. The simulation is performed using MATLAB-Simulink and SimPowerSystem Toolbox. The performance in steady and transient states show the efficiency and the simplicity of the proposed control scheme based on modified p-q control strategy. Before compensation the source voltage is much distorted with high THDv value equal to 46.93%. After compensation using proposed Series APF the THDv is reduced to 3.57% in conformity with 519-IEEE standard norms.
Article
Keywords: Series active power filter; Five-level (npc) inverter; Voltage disturbances compensation; Fuzzy logic control; Power quality improvement